DETERMINATION OF PARAMETERS OF TECHNOGENIC IRON-BEARING ROCKS BY COMPLEX RADIOACTIVE LOGGING (BY THE EXAMPLE OF TAILING DUMP OF NORTHERN MINE AND CONCENTRATOR COMPLEX) - Kamilova, O.; Kulyk, V.; Bondarenko, M.; Ketov, A.; Deineko, S. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
By means of a complex radioactive logging (RL) made up a neutron-neutron, gamma-gamma and gamma logging is executed research of rocks in the territory of tailing dump of Northern mine and concentrator complex. On the basis of objective and adaptable of RL-methodology (as sets of the corresponding methods and techniques) a number of petrophysical parameters of technogenic and natural rocks is determined and the content of iron is estimated. High efficiency and informativity of a RL-complex and its interpretative and methodical providing is shown.